Pengaruh Konflik Peran, Stress, Dan Dukungan Sosial Terhadap Komitmen Afektif Organisasi Pegawai Wanita (Studi Pada Pegawai Wanita Bank X Banjarmasin) - Dwiyanti, Lestari; Said, Laila Refiana; Dahniar, Dahniar (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2019)
This study aims to analyze the influence of role conflict and stress on the affective commitment of female employees with social support as a moderating variable in Bank X in Banjarmasin. This type of research is explanatory research with a quantitative approach. Respondents in this study were all female employees of the Bank X in Banjarmasin. The sampling technique used is a saturation sampling technique. Data collection uses a Likert scale scale questionnaire. Data analysis techniques using Partial Least Square (PLS) analysis techniques with SmartPLS 3.0 software. The results of the study concludes that there is a significant negative effect of role conflict on affective commitment  and there is a significant negative effect of stress on affective commitment. Other findings indicate that social support is able to act as a moderating variable on the influence of role conflict and stress on organizational affective commitment